PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMKN 1 BONJOL - Rahmi Wiyatri; Satrio Junaidi; Rini Novita (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aims to develop valid and practical interactive video learning media for informatics subjects using the Powtoon and H5P applications. This research uses Research and Development (R&D) research with the ADDIE development model which consists of 5 stages, namely: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The collection technique in the research was using a questionnaire. The results showed that interactive video learning media using the Powtoon and H5P applications based on the results of media validation by media experts obtained an average value of 0.82 in the